Adult Transition From At-Risk Drinking to Alcohol Dependence: The Relationship of Family History and Drinking Motives - Beseler, Cheryl L. (2008)
BACKGROUND: Prospective studies have not previously examined whether a family history of alcoholism and drinking motives conjointly predict a diagnosed DSM-IV alcohol abuse or dependence in adults, despite a large literature that each is associated with alcohol consumption. The focus of this study is the conjoint, prospective examination of these risk factors in a 10-year longitudinal study of adults who were at-risk drinkers at baseline. METHODS: Prospective, population-based cohort of drinkers aged 18 or older from a Northeastern U.S. area initially evaluated for history of alcohol use disorders and drinking motives in 1991 to 1992. New onset dependence was studied in those who never met the criteria for alcohol dependence at baseline (n = 423), and new onset abuse was studied in those who never met the criteria for alcohol abuse at baseline (n = 301) and who did not develop dependence during the follow-up. RESULTS: Family history significantly interacted with 2 baseline drinking motives in predicting new onsets of DSM-IV alcohol dependence: drinking to reduce negative affect (OR 3.38; 95% CI 1.05, 10.9) and drinking for social facilitation (OR 3.88; CI 1.21, 12.5). Effects were stronger after conditioning the drinking motives on having a positive family history of alcoholism. In contrast, in predicting new onsets of alcohol abuse, drinking motives did not have direct effects or interact with family history. CONCLUSIONS: Those who drank to reduce negative affect or for social facilitation at baseline were at greater risk of alcohol dependence 10 years later if they also had a family history of alcoholism. These results suggest an at-risk group that can be identified prior to the development of alcohol dependence. Further, the findings suggest utility in investigating the interaction of drinking motives with measured genetic polymorphisms in predicting alcohol dependence.